Dr. Ambedkar A Universal Educator - Tomer, Ritesh Singh (JOURNAL OF INDIAN EDUCATION, 2016)
Although Ambedkar, who spent more than forty years of his life in association with different educational institutions, holding disparate positions, has never been given the status of a mainstream educator, he has done work that is of fundamental importance in this regard. When India was in the process of becoming a modern nation state and universalisation of education was the task at stake, Ambedkar made sure that those who had remained ignored in the realm of education for centuries, no longer remained so. The role that Ambedkar played in the upliftment of Dalits of Hindu social order is an apparent example, but his efforts extended far beyond.